Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1055/s-0039-1697899
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ACL Reconstruction on Involved and Contralateral Limb Vastus Lateralis Morphology and Histology: A Pilot Study

Abstract: Quadriceps muscle weakness is a commonly reported issue post anterior cruciate ligament reconstruction (ACLR), with minimal information related to skeletal muscle morphology following surgery. The purpose is to examine the morphological and functional differences in the vastus lateralis muscle from patient's ACLR and contralateral leg. Three physically active ACLR participants were recruited and secured to a dynamometer to perform maximal voluntary isometric knee extension contractions (MVIC) of the ACLR and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
5
2
2
Order By: Relevance
“…62,84 These data suggest that evaluation of intramuscular fat content by means of ultrasound imaging may serve as a useful clinical measure. Previous studies have also reported acute 92 and persistent 93 atrophy among type IIa and IIx muscle fibers in the vastus lateralis following ACLR. In addition to a smaller fiber diameter, a metabolic shift has also been observed within the vastus medialis, such that the muscle becomes more endurant.…”
Section: Morphological Changesmentioning
confidence: 86%
“…62,84 These data suggest that evaluation of intramuscular fat content by means of ultrasound imaging may serve as a useful clinical measure. Previous studies have also reported acute 92 and persistent 93 atrophy among type IIa and IIx muscle fibers in the vastus lateralis following ACLR. In addition to a smaller fiber diameter, a metabolic shift has also been observed within the vastus medialis, such that the muscle becomes more endurant.…”
Section: Morphological Changesmentioning
confidence: 86%
“…Die beschriebene volumetrisch-numerische Typ-II-Faseratrophie des VM [32][33][34] oder VL [7] nach Verletzungen oder Erkrankungen des Kniegelenks konnten die Ergebnisse unserer Untersuchungen an insgesamt 20 Fußballspielern nach wiederholter ipsilateraler VKB-Ruptur nicht bestätigen [13]. Vermutlich sind Einflüsse wie Dauer der Immobilisation und Reduktion des Aktivitätslevels verantwortlich für die beschriebene Faseratrophie des VM.…”
Section: Muskelfaserleitgeschwindigkeit Und Muskelfaserquerschnittunclassified
“…Einzelne Beobachtungen an Leistungssportlern weisen jedoch, abhängig vom Ausmaß der Seitenpräferenz, auch Kraftwerte auf der betroffenen Seite auf, die über denen der nicht betroffenen Seite liegen [6]. Ein niedrigerer Frequenzinhalt des EMG-Leistungsspektrums des M. vastus medialis [3] belegt indirekt eine mögliche Veränderung des Faserspektrums der betroffenen Muskulatur [7]. Jedoch können sich Kompensationen infolge von Verletzungen auf unterschiedlichen Ebenen des neuromuskulären Systems manifestieren.…”
unclassified
“…What is currently known in the context of AMI is that muscle processes that are tightly regulated by neural signaling experience adaptations after injury. For instance, in patients with ACLR, investigators have reported that muscle undergoes adaptations in fiber-type expression [85][86][87] and becomes more fatty and fibrotic. 88 The accumulation of inhibited fibers 87 may disrupt the intracellular calcium signaling cascades, leading to adaptations in tissue quality and phenotypic expression in those with AMI.…”
Section: Influence Of Ami On Other Interconnected Systemsmentioning
confidence: 99%